Validation of PD-L1 clone 22C3 immunohistochemical stain on two Ventana DISCOVERY autostainer models: detailed protocols, test performance characteristics, and interobserver reliability analyses. (1st October 2020) - Basu, Atreyee; Chiriboga, Luis; Narula, Navneet; Zhou, Fang; Moreira, Andre L
ABSTRACT: Immunohistochemical (IHC) stain for PD-L1 as a biomarker for immunotherapy is recommended in non-small cell lung cancer (NSCLC). Under the FDA, the selection of patients for pembrolizumab requires companion diagnostic testing using the Dako Agilent PD-L1 IHC 22C3 pharmDx kit performed on the Dako Autostainer Link 48 platform. However, because it is not widely available, there is need for cross-platform validation. Existing studies provide incomplete protocol detail. In our study, 73 lung tumors were stained using the FDA-approved test ('gold standard'). The same blocks were stained using two different models of the Ventana DISCOVERY platform (ULTRA, n = 73 and XT, n = 70) using different parameters, and interpreted by three pathologists. The ULTRA group met College of American Pathologists (CAP) validation criteria (concordance 91.8%) while the XT group did not (concordance 67.1%). Using tumor proportion score (TPS) ≥1% and TPS ≥50% as cut-offs, the ULTRA protocol had higher sensitivity (97.8% and 91.7%) than XT (73.3% and 60.9%) and similar specificity (ULTRA 88.9% and 100%, XT 88% and 100%). Discordance between ULTRA and XT was 27%, and in all these cases ULTRA was concordant with gold standard. Interobserver reliability was substantial for ULTRA and almost perfect for XT, providing evidence that staining rather than observer variability accounts for XT's inferior performance. Cross-validation of the clinically used 22C3 anti PD-L1 antibody test with substantial interobserver agreement is possible on the commonly used the Ventana DISCOVERY ULTRA automated instrument, while the validation failed on the XT. Cautious attention to detail must be paid when choosing cross-validation parameters.